1996
DOI: 10.1007/3-540-61474-5_79
|View full text |Cite
|
Sign up to set email alerts
|

Atomicity refinement and trace reduction theorems

Abstract: Assertional methods tend to be useable for abstract, coarse~grained versions of concurrent algorithms~ but quickly become intractable for more realistic, finer-grained implementations. Various trace-reduction methods have been proposed to transfer properties of coarse-grained versions to finer-grained versions. We show that a more direct approach, involving the explicit construction of an (inductive) invariant for the finer-grained version, is theoretically more powerful, and also more appropriate for computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Lipton's reduction was refined multiple times [39,21,7,6,45]. Flanagan et al [11,15] and Qadeer et al [14,16,13] have most recently developed transactions and found various applications.…”
Section: Related Workmentioning
confidence: 99%
“…Lipton's reduction was refined multiple times [39,21,7,6,45]. Flanagan et al [11,15] and Qadeer et al [14,16,13] have most recently developed transactions and found various applications.…”
Section: Related Workmentioning
confidence: 99%
“…Lipton's reduction was refined multiple times [31,20,13,11,40]. It has recently been applied in the context of compositional verification [39].…”
Section: Related Workmentioning
confidence: 99%
“…These works have been extended by Doeppner, Schneider, Cohen and Lamport for different formalisms or different properties [Doe77,LS89,Gri96,CL98]. More recently, Freund, Qadeer and Flanagan [FQ03b,FQ03c,FQ03a] leveraged the Lipton's theory to detect transactions in multithreaded programs (and consider these transactions as atomic in the verification process).…”
Section: Introductionmentioning
confidence: 99%